Essential oil of Cinnamodendron dinisii Schwanke for the control of Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) - F. VEDOVATTO; C. VALÉRIO JÚNIOR; V. ASTOLFI; P.A.A. MIELNICZKI; S.S. ROMAN; N. PAROUL; R.L. CANSIAN (Universidade Estadual Paulista, 2015)
ABSTRACT The use of natural compounds is a less aggressive alternative for the control of insects in stored grains, in relation to synthetic chemical agents. Plants with insecticidal properties can be used as a source of these compounds to the direct application in pest control. In this work, the essential oil of Cinnamodendron dinisii was chemically characterized and tested regarding its insecticidal and repellent effect on the control of Sitophilus zeamais in stored grains. The essential oil was obtained by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS). The insecticidal potential was evaluated through the maintenance of the insects during 24 hours in contact with several doses of the oil, in the absence of feed substrate. The Bioassays of repellency were conducted with lethal doses (LD5, LD25, LD50 and LD95) obtained from insecticidal bioassay. In order to compare the treatments, the preference index (PI) was used. The essential oil of C. dinisii had insecticidal activity against S. zeamais, causing a linear and crescent mortality with LD of 0.04, 0.17, 0.34 and 0.63 µL/cm2, respectively. The repellency ranged from 55.4% to 85.2%, using the LD values previously mentioned. The DL5 was neutral regarding repellence (PI index -0,09), but from DL25 on, the PI index was between -0.1 and -1.0, indicating repellence activity.